The woman in suite 11 : a novel - Ware, Ruth (New York : Scout Press, 2025)
Journalist Lo Blacklock travels to a luxury Swiss hotel hoping to revive her career, but when a mysterious woman draws her into a dangerous chase across Europe, she must weigh ambition against survival in a world of wealth and shifting alliances.
Sequel to: The woman in cabin 10.
Keywords: Women journalists -- Fiction; Journalists -- Fiction; Travel writers -- Fiction; Hotels -- Fiction; Mistresses -- Fiction; Billionaires -- Fiction; Europe -- Fiction; Thrillers (Fiction); Psychological fiction